An in-depth cognitive examination of individuals with superior face recognition skills. (September 2016) - Bobak, Anna K.; Bennetts, Rachel J.; Parris, Benjamin A.; Jansari, Ashok; Bate, Sarah
Abstract: Previous work has reported the existence of "super-recognisers" (SRs), or individuals with extraordinary face recognition skills. However, the precise underpinnings of this ability have not yet been investigated. In this paper we examine (a) the face-specificity of super recognition, (b) perception of facial identity in SRs, (c) whether SRs present with enhancements in holistic processing and (d) the consistency of these findings across different SRs. A detailed neuropsychological investigation into six SRs indicated domain-specificity in three participants, with some evidence of enhanced generalised visuo-cognitive or socio-emotional processes in the remaining individuals. While superior face-processing skills were restricted to face memory in three of the SRs, enhancements to facial identity perception were observed in the others. Notably, five of the six participants showed at least some evidence of enhanced holistic processing. These findings indicate cognitive heterogeneity in the presentation of superior face recognition, and have implications for our theoretical understanding of the typical face-processing system and the identification of superior face-processing skills in applied settings.